Students' Interest in Learning Physical Education in Grade 7 Students of SMP Negeri 1 Kerinci Kanan: Minat Siswa Terhadap Pembelajaran Pendidikan Jasmani Pada Siswa Kelas 7 SMP Negeri 1 Kerinci Kanan - Khoirur Rois; Ricky Fernando (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
The problem behind this research is the results of observations where there are problems such as many students who are not serious, students are less enthusiastic in learning, learning methods that do not make students eager to learn and limited facilities and infrastructure for physical education practice. The purpose of this study was to determine students' interest in learning physical education in class 7 students at SMP Negeri 1 Kerinci Kanan. This type of research is descriptive quantitative. The population of this research is male students of SMP Negeri 1 Kerinci Kanan, totaling 22 students. The sample technique is a saturated sample with a total sample of 22 male students. The indicators of learning interest in the questionnaire were divided into 4 indicators, namely: 1) Feelings of pleasure, 2) student interest, 3) Attention, 4) student involvement. The initial items are 53 items and after the validity test it becomes 41 items. The results of this study are students' interest in learning physical education in grade 7 students of SMP Negeri 1 Kerinci Kanan with an average of 75% in the good category.